Preconception health and wellness: knowledge and attitudes of undergraduate women - Corbett, Elyse, author; Rickard, Kathryn, advisor; Amell, James, committee member; Bloom, Larry, committee member; Henry, Kimberly, committee member (Colorado State University. Libraries, 2011)
Despite recent acknowledgment of the importance of providing preconception care (PCC) to reproductive aged women, many women remain under-informed and underserved in this area. Guided by the tenets of the Information-Motivation-Behavioral Skills (IMB) model, the present study sought to evaluate the degree to which young, reproductive aged college women (n =203) are informed, motivated, and skilled to optimize preconception health. Overall, participants demonstrated low to moderate knowledge of issues related to preconception health, more favorable attitudes toward pregnancy prevention approaches, and propensities for reproductive health risk behaviors in several lifestyle areas. Improved dissemination of preconception health information to young women should include programming to increase the degree to which this population is motivated and skilled in optimizing reproductive health. Existing efforts and interventions to promote preconception health need to be expanded and new strategies developed.
Keywords: pregnancy; preconception; women; college; counseling